Inland Water Body Fraction Map for Canada and Adjacent Regions at 250-m Spatial Resolution - Shaheen Ghayourmanesh; Alexander P. Trishchenko; Calin Ungureanu (Canadian Journal of Remote Sensing)
We present a novel raster dataset of surface inland water body fraction over Canada and neighbouring regions, including the northern parts of the United States, as well as Greenland, Iceland, and the northeastern sector of Russia, at 250-m spatial resolution. It was derived from the Global Surface Water (GSW) dataset (version 5) using a two-step resampling to ensure an accurate replication of the original data and spatial consistency in terms of extent and resolution with the Long-Term Satellite Data Records derived from the Moderate Resolution Imaging Spectroradiometer (MODIS) and the Visible Infrared Imaging Radiometer Suite (VIIRS) sensors. Additional input data and several coastline vector shape databases were utilized to refine the delineation of waterbodies and land-ocean interface. The resulting dataset is an 8-bit signed integer map, where each pixel represents either the water fraction or a land/ocean mask. Positive values indicate water bodies within Canada, while negative values represent areas outside of Canada. This dataset provides a more precise and up-to-date tool for medium-resolution studies of surface inland water in Canada, aligning closely with satellite imagery of similar spatial resolution. The dataset is freely available through the Government of Canada’s Open Government Portal.